A philosophical framework on critical thinking for adult learners of entrepreneurship education - Laddaran, Joanna Rose T. (College of Education, University of the Philippines Diliman, 2019)
The rapidly changing business environment brings to fore the role of entrepreneurship education to equip adult learners aspiring to become entrepreneurs. This study explored on critical thinking as an integral part in the practice of entrepreneurship and as a fundamentals component in a philosophical framework for adult learners of entrepreneurship education. In particular, the study focused on adult learners engaged in the Start Your Own Business (SYOB) course in one institution located in Quezon City. Using conceptual analysis and the grounded theory approach, this study described the motivations and challenges of seventy-seven (77) adult learners of entrepreneurship education, and the conceptions of ten (10) educators on the role of critical thinking in entrepreneurship education. Results indicate that the motivations of adult learners in entrepreneurship education include their plan to start a business, and their aim of career advancement and personality development. The challenges faced by the adult learners include the course's emphasis on theoretical and technical terms, lack of interaction and in-depth discussions, limited time and complicated business plan requirement. Meanwhile, educators recognize that critical thinking is viral in entrepreneurship education as it assists adult learners to analyze, assess, reflect, discern and harness their problem-solving skills for decision making. Through the lens of philosophy of education, this study concludes with the formulation of a philosophical framework on critical thinking for adult learners of entrepreneurship education, ensuring that the aims, methods, and content of entrepreneurship education programs keep up with the needs of the ever changing business environment, and the continuously evolving needs of adult learners and their pursuit of lifelong learning.